Analysis of Volcanic Ash Dispersion from The Mount Agung Eruption Using Himawari-8 Satellite Data: Case Studies from 25 November 2017; 28 June 2018, and 4 July 2018 - Pratiwi, Ire; Kharisma, Sulton; Carine P.D.V, Maria (Pusat Penelitian dan Pengembangan BMKG, 2024)
The eruption of Mt. Agung in Bali province over the last two years caused Ngurah Rai International Airport in Bali province, Lombok International Airport in West Nusa Tenggara province, and Notohadinegoro Airport as well as Blimbingsari Airport, both in East Java province, close. The eruptions of volcanoes have a major impact on human activities as airplanes are the fastest and most efficient transportation. Volcanic ash can ruin the jet engine and lead to flameout. Accurate information on the movement and dispersion of volcanic ash was required, considering the location of Mt. Agung is far enough from the affected airports. One of the identifications of volcanic ash was processed using Himawari-8 satellite data with several channels. The satellite data was processed using TVAP (Three Band Volcanic Ash Product), Split Window, and RGB (Red Green Blue) techniques to get the result of the trajectory of volcanic ash dispersion. The result can be used as a reference in airport operations. It showed the movement and dispersion of volcanic ash from Mt. Agung’s eruption to the affected airport area, which resulted in the closure of the airports. The volcanic ash was dispersed in a west-southwest direction, impacting the central and southern regions of Bali Island.